Quantitave Estimation Of The Active Constituents Of Parkia Biglandulosa By Using HPTLC And FTIR - RUPESH. P; PAL.S.C; PAVANI.A; GADGE.M.S. (International Journal of Pharma and Bio Sciences, 2010)
Parkia biglandulosa, a native of Malaya. The genus is named after Mungo Park. It is a large handsome, evergreen tree. Flowers are small, ball-shaped, and brown initially turning to white, in pendant flower heads on long stalks. Flowering is in March to April. Propagation is by seeds. The plant is grown in gardens as ornamental tree and also on roadsides as avenue tree. Fruit pulp is reported to be edible. Pollen mixed with water makes a refreshing drink. The different parts of the plant shows anti ulcer activity, Antibacterial activity, antifungal activity, anti inflammatory activity etc. Saponin’s from the seed bran of Parkia biglandulosa is used medicinally in India for its astringent and detergent properties and also as a fish poison. lectins from Parkia biglandulosa also have mitogenicity and antiproliferative activity. This present research paper mainly focused on the quantitative estimation of its constituents by using HPTLC and FTIR. After the extraction with petroleum ether and methanol the active constituents were found to be sterols. Crude plant extracts are generally a mixture of active and non-active compounds. The quantitative estimation of all active constituents is very important for pharmacological point. The percentage compositions of the active constituents are as follows: Compesterol was found to be 0.026%, β-Sitosterol 0.074%, Lupeol 0.037%, Gallic acid 1.079%.